Financial Management and Marital Quality: A Phenomenological Inquiry - Emily D Baisden; Jonathan J Fox; Suzanne Bartholomae (Journal of Financial Therapy, 2018)
This study explores the link between couples’ financial management practices and their marital quality through qualitative inquiry. Six couples in their first marriage with at least one child age 18 or younger were interviewed to understand how the couples’ financial histories affect their current approach to financial management and how their financial management affects their relationships. Using Couples and Finances Theory as a conceptual framework, this phenomenological study investigates the connection between financial history, approach to financial management, and marital quality to offer implications for financial counselors and therapists. The ways couples manage their finances are diverse, as are the impacts on their relationships. Couples’ financial histories lead to diverse management processes influenced by financial stressors, communication, and shared values. Financial therapists and counselors should recognize that each person’s financial history affects the way they think about money, which can affect their ability to communicate about finances with a partner. Therapists can build on the experiences of couples reporting in this study to help alleviate financial stress, improve financial relationships, and ultimately enhance marital quality.
Keywords: financial management; financial history; money scripts; marital quality; qualitative study